Prescription pattern analysis of nonsteroidal anti-inflammatory drugs in the northeastern iranian population - Majid Zeinali; Jamshid Tabeshpour; Seyed Vahid Maziar; Zhila Taherzadeh; Mohammad Reza Zirak; Danielle Sent; Kamal Razavi Azarkhiavi; Saeid Eslami (Wolters Kluwer Medknow Publications, 2017)
Objective: Inappropriate nonsteroidal anti-inflammatory drugs (NSAIDs) therapy is a common cause of actual and potential adverse effects, such as bleeding and gastrointestinal ulceration, which exacerbates the patient's medical condition and might even be life threatening. We aimed to evaluate and analyze the prescription pattern of NSAIDs in Northeastern Iranian population and also provide suggestions for a more rational prescription behavior for such drugs. Methods: In this cross-sectional retrospective study, pattern of 1-year prescriptions was inspected based on 9.3 million prescriptions from two insurance companies. Type of NSAIDs, all dispensed doses and the number of NSAIDs ordered per prescription, and the route of administration for each patient were extracted from the databases. The prescription pattern of NSAIDs was analyzed seasonally. Findings: Out of 9,303,585 prescriptions, 19.3% contained at least one NSAID. Diclofenac was the most commonly prescribed NSAID (49.21%). At least two NSAIDs were simultaneously prescribed in 7% of prescriptions. General practitioners prescribed NSAIDs more frequently (67%) than specialists. Orthopedic surgeons and internists more frequently prescribed NSAIDs in comparison with other physicians (6% and 4%, respectively). Gastroprotective agents (GPAs) were coprescribed to only 7.62% of prescriptions. Conclusion: The frequency of NSAIDs prescription was relatively high in Northeast of Iran. A significant number of prescriptions were associated with irrational prescribing in both coadministration of NSAIDs and GPAs and NSAIDs combination. A strategy must be developed and implemented for prescribing and rational use of medications, e.g., continuing medical education regarding the potential risks of NSAIDs, importance of their appropriate and rational use, and necessity of appropriate prescription writing regarding both content and indication.